The Effectiveness of Productive Zakat Distribution on The Welfare Level of Mustahiq a Study at BAZNAS in Depok City - Khodijah Qodiryani, Masayu Ustadzah; Amelia, Erika (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
Poverty is the result of social problems and inequality in development. This is evidenced by an increase in unemployment of 9.87% and a decrease in people's income of 0.09% per capita. The existence of the Zakat Fund Policy managed by BAZNAS has succeeded in reducing the percentage of poverty by 0.05% in 2022. However, this decline is still far from recovering as before due to the inequality between urban and rural areas, in particular, Depok City, West Java, which has the smallest poverty percentage. This study aims to determine the effectiveness of zakat (DCR) and the BAZNAS Welfare Index (IKB) to calculate the welfare level of 100 Mustahiq. Then use a linear regression approach to find the effect. The results of the study prove that BAZNAS Depok City has an effectiveness in distributing zakat funds of 79%, and the results of the IKB assessment are declared good, which is 0.63. Therefore, with these data, it is proven that the effect of the effectiveness of distribution on the welfare level of Mustahiq is 79%. These results imply that the BAZNAS Depok City Zakat Distribution Program has been effective.